Faktor-Faktor Yang Mempengaruhi Respon Petani Padi Terhadap Sistem Tanam Jajar Legowo Di Nagari Singkarak Kecamatan X Koto Singkarak - Yesi Muhariyantika; Fuad Madarisa; Erigas Eka Putra (FAKULTAS ILMU ADMINISTRASI UNIVERSITAS LANCANG KUNING, 2022)
The purpose of this research is to 1) AnalyzeThe influence between farmer characteristics and the response of rice farmers to the Jajar Legowo Planting System in X Koto Singkarak District. 2)Analyzingthe effect of the nature of innovation with the response of rice farmers to the Jajar Legowo Planting System in X Koto Singkarak District. 3)Analyzing the influence between the role of extension workers and the response of rice farmers to the Jajar Legowo Planting System in X Koto Singkarak District.The population in this study are farmers who are members of farmer groups who are trying to grow rice using the Jajar Legowo Planting System in Nagari Singkarak District X Koto Singkarak,the population of 9 rice farmer groups is 219 people. The sample was calculated using the Slovins formula with a total of 69 people. The data analysis used in this study is a quantitative descriptive analysis andMultiple linear regression analysis. Based on the results of the analysis and discussion, some conclusions can be drawn as followsCharacteristic factors of members of the age group and length of farming have a significant effect on the response of rice farmers to the jajar legowo planting system partially, while the characteristics of members of the formal education group, land area and number of family dependents have no significant effect on the response of rice farmers to the jajar legowo planting system in general. partial, the nature of innovation has a significant effect on the response of rice farmers to the jajar legowo planting system partially then the role of extension workers has a significant effect on the response of rice farmers to the jajar legowo planting system partially